Influencia del control previo en la ejecución del gasto de la Municipalidad Provincial de Requena periodo 2014 – 2018 - Pacaya Ahuite, Glenn Ricky (2024)
The main problem was to evaluate the influence of prior control in the execution of the expenditure of the provincial municipality of Requena period 2014 - 2018. The objective of the study is to evaluate the influence of prior control in the execution of expenditure. In relation to the objective, the quantitative study has been carried out, descriptive level with non experimental design. The most important results are related to the permanent training in budget, administrative systems, norms and internal directives related to the efficient management of public resources, 72% of the respondents indicated that they are trained. In addition, 100% of the study population has received training on spending execution issues and 88% on spending execution follow-up issues. The investigation concludes that the entity emphasizes the training of its personnel, the knowledge of internal norms and directives for the management of public resources, as well as the source documents of the expense. In relation to prior control, 52% have indicated that in certain cases the standards are met, a fact that leads to having expenses with missing source documentation. Finally, accrued expenses have sufficient source documentation to be processed in the Integrated Administrative System (SIAF) and sometimes these records are modified.